2023
DOI: 10.1177/20406207231154713
|View full text |Cite
|
Sign up to set email alerts
|

Superior survival outcome of blinatumomab compared with conventional chemotherapy for adult patients with relapsed or refractory B-cell precursor acute lymphoblastic leukemia: a propensity score–matched cohort analysis

Abstract: Background: Blinatumomab showed a higher complete remission (CR) rate and a safe bridging to allogeneic hematopoietic cell transplantation (allo-HCT) in adults with relapsed or refractory B-cell precursor acute lymphoblastic leukemia (R/R BCP-ALL). Objectives: We tried to analyze the outcome of blinatumomab compared with the real-world historical data. We expected superior outcome of blinatumomab compared with historical conventional chemotherapy. Design: We conducted a retrospective study using real-world dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…Single arm studies showed an overall response of 44.9% but a higher response rate (68.8%) was observed when patients were treated in first-line salvage [ 152 , 153 ]. A more recent matched cohort comparative study reported a very good overall response rate (80.8 vs. 53.8%) with lower regimen-related death rate (1.9 vs. 40.4%) compared to historical standard chemotherapy such as the MEC regimen [ 154 ]. Comparative data revealed a 3-year OS of 33.2% with a median OS of 26.3 months, which was significantly superior compared to the historical control ( Fig.…”
Section: Salvage Therapy For R/r Allmentioning
confidence: 99%
“…Single arm studies showed an overall response of 44.9% but a higher response rate (68.8%) was observed when patients were treated in first-line salvage [ 152 , 153 ]. A more recent matched cohort comparative study reported a very good overall response rate (80.8 vs. 53.8%) with lower regimen-related death rate (1.9 vs. 40.4%) compared to historical standard chemotherapy such as the MEC regimen [ 154 ]. Comparative data revealed a 3-year OS of 33.2% with a median OS of 26.3 months, which was significantly superior compared to the historical control ( Fig.…”
Section: Salvage Therapy For R/r Allmentioning
confidence: 99%